PENDEKATAN FIKIH DALAM PENGEMBANGAN PENDIDIKAN ISLAM BERBASIS GENDER DI PESANTREN MODERN - Nur Aqmarina, Devi; Achmad, Mukhsin (IAIN Madura, 2025)
This research discusses the transformation of gender-based Islamic education in modern pesantren that integrate gender equality in the curriculum, teaching methods, and fiqh. As a result, pesantren produce outstanding graduates who are aware of gender equality, although they still face cultural and structural obstacles. Gender fiqh-based solutions are proposed to create inclusive education.